2020
DOI: 10.1038/s41467-020-14950-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell-type specific nucleosome positioning in inducible activation of mammalian promoters

Abstract: The organization of nucleosomes across functional genomic elements represents a critical layer of control. Here, we present a strategy for high-resolution nucleosome profiling at selected genomic features, and use this to analyse dynamic nucleosome positioning at inducible and cell-type-specific mammalian promoters. We find that nucleosome patterning at inducible promoters frequently resembles that at active promoters, even before stimulusdriven activation. Accordingly, the nucleosome profile at many inactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 96 publications
(145 reference statements)
1
20
0
Order By: Relevance
“…The maintenance of nucleosome phasing, and the presence of a constitutive NDR in particular, is consistent with a model in which Bz promoters are structurally poised for activation already prior to stage conversion. This would be similar to observations at stimulus-inducible cell-type–specific promoters in mammals ( Oruba et al., 2020 ), where the magnitude of transcription after activation has been shown to correlate with promoter nucleosome depletion ( Scruggs et al., 2015 ). The transcription factors bound at these NDRs and the chromatin remodelling factors involved in maintaining nucleosome patterning at Bz promoters remain to be identified.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The maintenance of nucleosome phasing, and the presence of a constitutive NDR in particular, is consistent with a model in which Bz promoters are structurally poised for activation already prior to stage conversion. This would be similar to observations at stimulus-inducible cell-type–specific promoters in mammals ( Oruba et al., 2020 ), where the magnitude of transcription after activation has been shown to correlate with promoter nucleosome depletion ( Scruggs et al., 2015 ). The transcription factors bound at these NDRs and the chromatin remodelling factors involved in maintaining nucleosome patterning at Bz promoters remain to be identified.…”
Section: Discussionsupporting
confidence: 86%
“…Stage-specific data on transcription initiation also enabled us to compare nucleosome positioning at active and inactive Toxoplasma promoters. Studies in yeast and metazoans showed that nucleosome phasing and transcriptional activity are correlated and co-dependent ( Tirosh and Barkai, 2008 ; Weiner et al., 2010 ; Oruba et al., 2020 ). Accordingly, inactive promoters are often characterized by minimal nucleosome phasing and the lack of an NDR ( Mellor, 2005 ; Li et al., 2007 ; Lin et al., 2007 ; Jiang and Pugh, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…S3 ) . Our work in human cells as well as recently published work from the van Essen lab indicates that the proportion of inducible promoters is relatively small in the scope of all ∼21,000 human genes and that chromatin structural changes may occur with or without concurrent changes in gene expression ( Oruba et al , 2020 , Dennis lab, unpublished). This prompted us to look at nucleosome sensitivity dynamics during the immune response to HKST.…”
Section: Resultsmentioning
confidence: 59%
“…Therefore, it appears that mechanisms for constitutive nucleosome depletion are less often hard-wired by directly remodeler-recognized sequences, but rather that regulatable mechanisms of indirect remodeler-recruitment, e.g., via transcription factor binding sites or by recruitment via histone-modifcations, open promoter chromatin on demand. Recently, an in-depth in vivo analysis of promoter nucleosome organization in two different human cell types, each with and without cell-type-specific gene induction stimuli, demonstrated cell type-specific, induction-specific and even very transient promoter opening [112].…”
Section: Species-specific Strategies For Nucleosome Depletionmentioning
confidence: 99%